Effects of Water Yam and Corn Starches on the Interacting Variables Influencing the Disintegration of Chloroquine Phosphate Tablets - Okunlola, Adenike; Odeku, Oluwatoyin A (Dhaka University Journal of Pharmaceutical Sciences, 2012)
The individual and effects of interaction of nature (X) and concentration (Y) of disintegrant and the relative density (Z) on the mechanical and release properties of chloroquine phosphate tablets were studied using a 23 factorial experimental design. Water yam starch (“low” level) and corn starch (“high” level) were used as disintegrants at concentrations of 5.0% and 20.0% w/w. The mechanical properties were assessed using the crushing strength (CS) and friability (F) and the release properties by the disintegration time (DT) and dissolution time (t80). Increasing the concentration of disintegrants and the relative density of tablets resulted in increase in CS, but decrease in F, DT and t80. The ranking of the individual coefficient values was Z >X >Y for CS, Z > X>Y for F and DT, and Y>X>Z for t80 while that for the interaction coefficient was X-Z> Y-Z > X-Y for CS, Y-Z> X-Z > X-Y for F, Y-Z> X-Y> X-Z for DT and t80. Changing the disintegrant from corn starch to water yam starch resulted in decrease in CS, DT and t80 but increase in F. The results showed considerable interaction between the variables employed and suggested that water yam could be an alternative disintegrant to corn starch particularly where faster disintegration and release are required. DOI: http://dx.doi.org/10.3329/dujps.v10i1.10011 DUJPS 2011; 10(1): 21-28